The Impact of Changes from Water Transportation to Land Transportation in Selat District, Kapuas Regency in 1998-2024 - Rudy Prasetyo; Rochgiyanti Rochgiyanti; Mansyur Mansyur; Mohamad Zaenal Arifin Anis (JURNAL PENDIDIKAN IPS, 2025)
The change from water transportation to land transportation in Selat District, Kapuas Regency is caused by the development of land road infrastructure carried out by the Kapuas Regency Regional Government. This has an impact on the decline of water transportation which was previously the main mode of community mobility. The purpose of this study is to examine the impact of the change from water transportation to land transportation for the community in Selat District, Kapuas Regency from 1998-2024. This research uses a historical method consisting of four stages, namely heuristic, criticism, interpretation, and historiography. The results of the study show that this change has a positive and negative impact on the community in Selat District. The positive impact is the increase in accessibility and mobility of the community, which is supported by an increase in the number of land vehicles. Based on data from the Central Statistics Agency of Kapuas Regency, it shows that the number of land vehicles has increased significantly from 2019 to 2023. The number of land vehicles increased from 2,800 units in 2019 to 4,389 units in 2023. The increase in land transportation shows that the community's dependence is increasing, but it has an impact on decreasing water transportation, reducing jobs, and increasing traffic density. The conclusion reached is that this change is due to the development of road infrastructure that improves accessibility and mobility, but also brings social and economic impacts to communities that previously relied on water transportation.